2016
DOI: 10.1007/s10567-016-0201-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial–Ethnic Protective Factors and Mechanisms in Psychosocial Prevention and Intervention Programs for Black Youth

Abstract: Extending previous reviews related to cultural responsiveness in the treatment of ethnic minority youth, the current review provides a critical assessment and synthesis of both basic and applied research on the integration of three racial-ethnic protective factors (racial identity, racial socialization, Africentric worldview) in psychosocial prevention and intervention programs for Black children and adolescents. Seventeen programs meeting inclusion and exclusion criteria were evaluated for the extent to which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 106 publications
0
49
0
Order By: Relevance
“…Although racial-ethnic socialization and racial ethnic identity interlink to influence youth's developmental outcomes (Hughes et al, 2016), the extant research has tended to investigate these constructs and their effect on youth's outcomes separately (Jones & Neblett, 2016). We therefore used path analysis to investigate the interrelationships between RES, REI, and academic performance in one model to ascertain whether when considered simultaneously they have direct and/or mediated effect associations with the academic performance of African American youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although racial-ethnic socialization and racial ethnic identity interlink to influence youth's developmental outcomes (Hughes et al, 2016), the extant research has tended to investigate these constructs and their effect on youth's outcomes separately (Jones & Neblett, 2016). We therefore used path analysis to investigate the interrelationships between RES, REI, and academic performance in one model to ascertain whether when considered simultaneously they have direct and/or mediated effect associations with the academic performance of African American youth.…”
Section: Discussionmentioning
confidence: 99%
“…Although distinct conceptually, racial-ethnic socialization (RES) and racial-ethnic identity (REI) are inseparable and mutually related in practice (Hughes et al, 2016). However, analytically the extant research has typically treated them completely separately when considering culturally relevant protective factors in the development of African American children and youth (Jones & Neblett, 2016). Additionally, explorations of the subdomains of RES and REI have generally focused on the independent effects of their various subconstructs, although emerging evidence suggests these various subdimensions work together to influence children's developmental outcomes, including educational performance (Hughes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This specific intervention project showed that culturally focused interventions do have a place in school settings. Therefore, it is critical for school‐based practitioners and researchers to understand and incorporate issues of culture and racial aspects of socialization when studying Black youth development (Jones & Neblett, ; Worrell, ). The significant and practically meaningful gains in students’ Afrocentric world view were promising given the constructs related to positive outcomes in the empirical literature (Neblett, Seaton, Hammond, & Townsend, ; Williams & Chung, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not been the case in school psychology journals (Worrell, ). This is unfortunate because having a strong racial identity, which is defined as the degree to which an individual feels a connection with and an attachment to their racial group based on a common history and shared values, has shown to be a protective factor for people of color in general (Jones & Neblett, ). For Black children in particular, having a strong Black identity has been linked to a myriad of positive outcomes, including increased academic engagement, decreased drug use, and improved self‐esteem (Belgrave, Brome, & Hampton, ; Constantine, Alleyne, Wallace, & Franklin‐Jackson, ).…”
Section: Identity Development and Black Youthmentioning
confidence: 99%
See 1 more Smart Citation